The National Health Service - Great Britain. Central Office of Information. (London : His Majesty's Stationery Office, 1948)
1948 1948 1940s 38 pages two chemists, two 'persons with experience in mental health services', and five others (not doctors) with experience in local government. The Council advises the Minister not only on questions about which he asks for advice, but on anything about which it thinks he needs advice. There are also various standing committees to advise him on special questions — medical, dental, pharmaceutical, ophthalmic, nursing, maternity and midwifery, tuberculosis, mental health, and cancer and radiotherapy. They include members of the Central Health Services Council and others with special knowledge of their subjects. The Council and the standing committees also set up additional committees for special purposes as need arises. The Council has to make a yearly report on its work and that of the standing committees, and the Minister has to present the report to Parliament. In this way the public will know what his advisers have been telling him. There is the usual legal safeguard that the Minister may refuse to publish something in the report if, after consulting the Council, he is 'satisfied that it would be contrary to the public interest'. This is to prevent the leakage of such things as military secrets. In the health services this safeguard will very rarely be necessary and will probably never be used except with the agreement of the Council. If the Minister wishes, as he may wish if he disagrees with some advice given him, he can add his own comments to the report, so that the public will know what he feels about the advice offered him. The pay and conditions of all workers in the different branches of the services will in varying degrees be nationally regulated (a national superannuation scheme for the whole Service has already been created). For this purpose a system of Whitley Councils is being set up aiming to cover the whole Service. At the centre there are separate national 'functional' councils for opticians, pharmacists, nurses and midwives (including health visitors and nursery nurses), other professional and technical workers (such as laboratory workers), ancillary workers (such as ambulance drivers and ward maids), and administrative and clerical staffs. Each council has its employers' side and its staff side (drawn from the various professional organisations and unions). There is also a General Council to deal with problems affecting directly more than one of the functional councils, and these together form the 'Whitley Councils for the Health Services'. The tasks of this organisation for bringing managers and staffs together are to enable all who work in the Service to help in improving its efficiency ; to give them a ready channel for complaints and the remedying of any grievances ; and to undertake collective bargaining about matters of pay and conditions of work. Experience of Whitley Councils in industry and in national and local government service shows that nearly all such matters can be settled by agreement. But if there are disputes, and if they cannot be settled by agreement, they will usually be 33 21/1489